Combining Music and Indoor Spatial Factors Helps to Improve College Students’ Emotion During Communication - Jiang, Jiani; Meng, Qi; Ji, Jingtao (Frontiers in Psychology, 2021)
Against the background of weakening face-to-face social interaction, the mental health of college students deserves attention. In terms of emotional perception in a specific space, there are few existing studies on the impact of audiovisual interaction on interactive behavior. This study investigates the effects of music on college students’ communicating emotion using the three-dimensional pleasure–arousal–dominance emotional model in different indoor spaces, in terms of spatial function, visual and sound atmosphere, and interior furnishings. An acoustic environment measurement was employed, and a questionnaire survey was administered to 331 participants at six experimental sites (classroom, learning corridor, coffee shop, fast food restaurant, dormitory and living room). The following results were found. First, there was no significant effect of music on musical evaluation or communicating emotion in different functional spaces. Second, the average score for musical evaluation was 1.09 higher in warm spaces. Third, the differences in the effects of music on communication in different sound environments were significant, indicating that pleasure, arousal and dominance could be efficiently enhanced by music in quiet spaces. Fourth, dominance was 0.63 higher in spaces that had been furnished simply. We also investigated whether social characteristics had an influence on the effect of music on communication, and the results show that dominance was 0.40 higher when all the communicators were of the same gender. This study shows that combining the sound environment with spatial factors (for example, visual and sound atmosphere) and interior furnishings can be an effective design strategy for promoting social interaction in indoor spaces.